2012
DOI: 10.1038/nsmb.2379
|View full text |Cite
|
Sign up to set email alerts
|

BIRC7–E2 ubiquitin conjugate structure reveals the mechanism of ubiquitin transfer by a RING dimer

Abstract: Certain RING ubiquitin ligases (E3s) dimerize to facilitate ubiquitin (Ub) transfer from ubiquitin-conjugating enzyme (E2) to substrate, but structural evidence on how this process promotes Ub transfer is lacking. Here we report the structure of the human dimeric RING domain from BIRC7 in complex with the E2 UbcH5B covalently linked to Ub (UbcH5B∼Ub). The structure reveals extensive noncovalent donor Ub interactions with UbcH5B and both subunits of the RING domain dimer that stabilize the globular body and C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
444
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(474 citation statements)
references
References 56 publications
(104 reference statements)
27
444
3
Order By: Relevance
“…The structures of two dimeric RING E3s in complex with UBE2D‐Ub have been reported recently, and both show that the proximal RING binds the ubiquitin intermediate via ubiquitin's I36 surface patch. An aromatic residue from the distal RING makes additional contacts with the same ubiquitin surface, thereby stabilizing a “closed” conformation in which the E2~Ub is activated for transfer (Dou et al , 2012; Plechanovova et al , 2012). Similarly, in the TRIM25/E2~Ub structure each ubiquitin molecule is folded back onto its E2 in a conformation that resembles the one seen in other dimeric RING/E2~Ub complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of two dimeric RING E3s in complex with UBE2D‐Ub have been reported recently, and both show that the proximal RING binds the ubiquitin intermediate via ubiquitin's I36 surface patch. An aromatic residue from the distal RING makes additional contacts with the same ubiquitin surface, thereby stabilizing a “closed” conformation in which the E2~Ub is activated for transfer (Dou et al , 2012; Plechanovova et al , 2012). Similarly, in the TRIM25/E2~Ub structure each ubiquitin molecule is folded back onto its E2 in a conformation that resembles the one seen in other dimeric RING/E2~Ub complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, R54 of TRIM25, referred to as the linchpin for allosteric activation of E2~Ub (Pruneda et al , 2012; Metzger et al , 2014), is involved in electrostatic interactions with Q92 of UBE2D1 and Q40 and R72 of ubiquitin, and accordingly, its mutation reduces catalytic activity in discharge assays and formation of K63‐linked chains by UBE2N/UBE2V1 (Fig 4B–D). In contrast, the aromatic residue from the distal RING (Y193 of RNF4 and F296 in BIRC7), that is important in other RINGs to engage ubiquitin in the closed conformation, does not exist in TRIM25 (Dou et al , 2012; Plechanovova et al , 2012). Instead, residues K65 and T67 of the RING domain contact D32 and E34 of the opposite, distal ubiquitin in one monomer, whereas in the other monomer, the K65 and D32 interaction is absent and replaced by a hydrogen bond between N71 of the RING and K33 of ubiquitin (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…1A)-have been more closely examined for their role in ubiquitination mediated by distinct E2 ubiquitin-conjugating enzymes and E3 enzymes (e.g., refs. [22][23][24][25][26][27][28][29][30][31]. Notably, patch II but not patch I was shown to be required for covalent attachment of ubiquitin to substrate proteins catalyzed by the HECT E3s Rsp5 and NEDD4L (22,30).…”
Section: Resultsmentioning
confidence: 99%
“…In several instances, it has been shown that dimeric E3s require dimerization for ubiquitination activity (Dueber et al, 2011;Dou et al, 2012a;Plechanovová et al, 2012). Elegant experiments by Plechanovová et al (2012) and Dou et al (2012b) showed that the E2 contacts a single protomer of the dimeric E3 (RNF4 and Birc7, respectively), while ubiquitin is folded back onto the E2 via contacts from both RING molecules.…”
Section: Dimerization and E3 Ligase Activitymentioning
confidence: 99%
“…In several instances, homooligomerization was shown to influence the activity of both self and substrate ubiquitination. Mutant variants that were impaired in their oligomerization displayed reduced activity (Yin et al, 2009;Dueber et al, 2011;Plechanovová et al, 2011;Dou et al, 2012a). Exceptions include the U-box E3s E4B in humans and its ortholog Ufd2 in yeast (Saccharomyces cerevisiae), which function as monomers (Benirschke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%